The Homelanders: The Truth of the Matter - Book 3 - Klavan, Andrew (Nashville, Tenn. : Thomas Nelson, 2010)
When eighteen-year-old Charlie West finds the one person who knows what happened to him a year earlier, he learns that remembering is painful as well as dangerous, and figuring out what to do with the new knowledge may be his toughest challenge yet.
Keywords: Amnesia -- Fiction; Terrorism -- Fiction; Adventure fiction